Consumer food demand in Japan before and after the beginning of COVID-19: AIDS analysis using home scan data - Ito, Nobuhiro; Maruyama, Yuki; Wakamatsu, Hiroki (Frontiers in Sustainable Cities, 2022)
The COVID-19 has not only had impact on human health, but also consumers’ food consumption. Employing the Almost Ideal Demand System (AIDS), this study analyzes whether consumers change their demand for food between 2019 and 2020 in Japan where the consumerslegal action was not implemented to restrict consumer behavior are not forced to go out for shopping. Using the home scan data, 25 food items including eating-out and delivery are analyzed to see the impact of the COVID-19. Results show that the increase in shares of expenditure are mainly related to consumption in the home in 2020, while that for eating-out turned into a significant decrease. The estimated own price elasticity and expenditure elasticity of demand show that ingredients for home-cooking are more substitutive with eating-out and more complemental within the ingredients in 2020.